Exploring Indeno[2,1-c]fluorene Antiaromatics with Unsymmetrical Disubstitution and Balanced Ambipolar Charge-Transport Properties - Sharma, Himanshu; Ankita, Ankita; Bhardwaj, Pooja; Pandey, Upendra Kumar; Das, Soumyajit (Organic Materials, 2023)
Unsymmetrically disubstituted antiaromatic indenofluorene (IF), in comparison to aromatic pentacene counterpart with unsymmetrical disubstitution, was rare in the literature until our recent report on indeno[1,2-b]fluorene and indeno[2,1-a]fluorene. Described herein is a straightforward access to unsymmetrically disubstituted indeno[2,1-c]fluorenes bearing mesityl at one apical carbon and C6F5, 3,5-(CF3)2C6H3, and CCSii-Pr3 at the other apical carbon, including 4-methoxyphenyl/3,5-(CF3)2C6H3 push/pull substitution at the apical carbons with appreciable orbital density, and a previously unknown symmetrically C6F5-disubstituted [2,1-c]IF. The electronic properties of the unsymmetrical derivatives lie halfway in between the two symmetrical counterparts, while the 4-methoxyphenyl derivative showed the smallest HOMO–LUMO energy gap and near-infrared absorption with intramolecular charge transfer character. Single-crystal analyses showed 1D-columnar stacks for the unsymmetrical motif with the C6F5 units co-facially π-stacked with the IF core, whereas symmetrically C6F5-disubstituted [2,1-c]IF, with a low-lying LUMO, showed intermolecular π–π stacks between the IFs that resulted in good electron mobility (µe = 8.66 × 10−3 cm2 · V−1 · s−1) under space charge limited current measurements. Importantly, balanced ambipolar charge-transport behaviour could be extracted for an IF series with symmetrical/unsymmetrical substitutions, in comparison to its π-contracted pentalene congener.
Keywords: indenofluorenes; indacene; polycyclic antiaromatics; ambipolar charge-transport; charge-carrier mobility; optoelectronic properties